Lithiumpyridinyl‐Driven Synthesis of High‐Purity Zero‐Valent Iron Nanoparticles and Their Use in Follow‐Up Reactions. Issue 37 (22nd July 2019) - Egeberg, Alexander; Block, Theresa; Janka, Oliver; Wenzel, Olivia; Gerthsen, Dagmar; Pöttgen, Rainer; Feldmann, Claus
Abstract: The synthesis of zero‐valent iron (Fe(0)) nanoparticles in pyridine using lithium bipyridinyl ([LiBipy]) or lithium pyridinyl ([LiPy]) is presented. FeCl3 is used as the most simple starting material and reduced either in a [LiBipy]‐driven two‐step approach or in a [LiPy]‐driven one‐pot synthesis. High‐quality nanoparticles are obtained with uniform, spherical shape, and mean diameters of 2.9 ± 0.5 nm ([LiBipy]) or 4.1 ± 0.7 nm ([LiPy]). The as‐prepared, high purity Fe(0) nanoparticles are monocrystalline. In addition to particle characterization (high‐resolution transmission electron microscopy, scanning transmission electron microscopy, dynamic light scattering), composition and purity are examined in detail based on electron diffraction, X‐ray powder diffraction, elemental analysis, infrared spectroscopy, 57 Fe Mössbauer spectroscopy, and magnetic measurements. Due to their small size and high purity, the Fe(0) nanoparticles are highly reactive. They can be used in follow‐up reactions to obtain a variety of iron compounds, which is exemplarily shown for the transformation to iron carbide (Fe3 C) nanoparticles, the reaction with sulfur to obtain FeS nanoparticles, or the direct reaction with pentamethylcyclopentadiene to FeCp*2 (Cp*: pentamethylcyclopentadienyl). Abstract : Zero‐valent iron nanoparticles are obtained by novel lithium‐pyridinyl‐driven reduction of FeCl3 in pyridine. The Fe(0) nanoparticles are characterized by high purity, small size (3–4 nm), and high reactivity. Direct follow‐up reactions to iron compounds such as Fe3 C nanoparticles, FeS nanoparticles, or FeCp*2 is possible.